Online Science Teaching Success is Pre-Determined by Pedagogical & Technological Preparations - M. Alforque, Jonemel (ASEAN Journal of Education, 2023)
Online science learning is a new educational norm adapted at the start of the COVID-19 pandemic in the Philippines. This study aimed to investigate the experiences of grade school science teachers through interpretative phenomenological analysis. Five (5) teacher-participants who were on the forefront of preparation, implementation, and evaluation of online science learning were selected and interviewed on March 7-11, 2022. Results implied that a thorough preparation on the pedagogies, curriculum, technologies, and training of skills are crucial in the implementation of the learning modality. These are factors that require the collaboration and establishing of guidelines among school stakeholders (faculty, parents, support staff, and administrators) to be successfully implemented. When shifting to online science learning, schools need to prepare by taking into consideration the following: 1) Redetermine the curriculum; the coverage (breadth and depth) should focus on the grade level competencies and topics that are pre-requisites to the next level; 2) Redefine the teaching-learning pedagogies and academic guidelines; the delivery of the lesson, activities, and assessments should be flexible to the online environment and learners’ context; 3) Acquire appropriate technologies such as computers for teachers and learning management system that suits the remodeled curriculum and redefined pedagogies; 4) Provide adequate training for teachers and support staff in the use of technology, planning and implementation of the lesson, and providing holistic supervision and assistance to pupils; and 5) Orient the parents and the pupils with curriculum, pedagogy and academic guidelines, required technologies, and skills.